vì \(n-1⋮n-1\)\(\Rightarrow2\left(n-1\right)⋮n-1\)\(\Rightarrow2n-2⋮n-1\)
\(\Leftrightarrow\left(2n+3\right)-\left(2n-2\right)⋮n-1\)
\(\Leftrightarrow5⋮n-1\)
\(\Leftrightarrow n-1\inƯ\left(5\right)\)mà \(x\in N\)
\(n-1\in\left\{1;5\right\}\)
ta có bảng:
n-1 | 1 | 5 |
n | 2 | 6 |
vậy \(x\in\left\{2;6\right\}\)
Có:
2n+3=2(n-1)+5
Vì 2(n-1) chia hết cho n-1
=>5 chia hết cho n-1
=>n-1 là Ư(5)
=>Ư(5)={-1;1;-5;5}
NX:
+)n-1=-1=>n=0(tm)
+)n-1=1=>n=2(tm)
+)n-1=-5=>n=-4(loại)
+)n-1=5=>n=6(tm)
Vậy...
ai mà cứ k sai vậy có giỏi thì chỉ cho mik lỗi sai đi :P